Saline-sodic soil treated with gypsum, organic sources and leaching for successive cultivation of sunflower and rice - Petrônio D. dos Santos; Lourival F. Cavalcante; Hans R. Gheyi; Geovani S. de Lima; Everaldo M. Gomes; Francisco T. C. Bezerra (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Correction of saline and sodic soils aims to reduce salts dissolved in the solution and exchangeable sodium, respectively, to allow the growth and production of crops. In this context, an experiment was carried out between August/2011 and September/2012, in saline-sodic soil of the Irrigated Perimeter of São Gonçalo, in the municipality of Sousa, PB, Brazil. Agricultural gypsum, organic sources and continuous leaching for reducing salinity, sodicity and alkalinity in the saline-sodic soil and their effects on the production of the sunflower cultivar Embrapa 122/V-2000 and the rice variety Diamante were evaluated. The treatments were distributed in four randomized blocks and the soil was subjected to continuous leaching for 50 days and evaluated for salinity, sodicity and alkalinity before and after leaching, as well after sunflower and rice cultivation, in the 0-0.20 and 0.20-0.40 m layers. Leaching and the application of gypsum and organic sources reduced the initial salinity in both soil layers, to a greater extent in the surface layer. Exchangeable sodium decreased in 0-0.20 m and increased in 0.20-0.40 m. After rice cultivation, the soil in the 0-0.20 m layer changed from saline-sodic to non-saline in the treatments gypsum + bovine manure and gypsum + rice husk. The reduction of salinity, sodicity and alkalinity in the soil was higher during rice cultivation than during sunflower cultivation.